Correlation between Neck Circumference and Continuous Positive Airway Pressure among Patients of Obstructive Sleep Apnea - Faisal Asad, Abdul Aziz Sahito, Fasih-Ur-Rahman, Madiha Moin, Ubedullah, Saif-Ur-Rahman, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To investigate the relationship between neck circumference (NC) and continuous positive airway pressure (CPAP) in patients with obstructive sleep apnea (OSA), as well as to assess CPAP requirements based on the neck circumference. Material and methods: This study was carried out in the pulmonary, vascular, and sleep disorders department of the Dow University Hospital in Karachi. The study was done for six months of duration from January 2022 to June 2022. All of the patients who had obstructive sleep apnea (OSA), between the ages of 18 and 60 years, both genders and underwent CPAP therapy were chosen for this study. The polysomnography database was utilized in order to do an analysis on the Apnea-Hypopnea Index for the OSA. Neck circumference was measured at the neck’s middle sit in every participant. The neck circumference was correlated with the CPAP therapy. The structured study proforma was used to collect all the data. Results: A total of 181 individuals who presented with OSA were studied. Mean age of the cases were 52.86+12.26 years and mean neck circumference was 43.45+3.58 cm. Males were 58.0% and females were 42.0%. Majority of the cases 56.4% had severe OSA. There was a strong significant positive correlation between neck circumference and CPAP (r= 0.177, p-value 0.017) and significant positive correlation between neck circumference and CPAP (r= 0.366, p-value 0.001). Average of CPAP pressure was significantly high according to severity of OSA (p-0.0001). Conclusion: The neck circumference was observed to be the most reliable marker that significantly positively correlated with CPAP therapy and measurements of OSA and its severity, by AHI alone, seem to have a positive correlation with CPAP therapy. However, OSA evaluation and treatment can be measured for their responsiveness to CPAP based on their neck circumference. Keywords: OSA, NC, CPAP, Relationship